Soy intake and breast cancer risk: a meta-analysis of epidemiological studies - Bahrom, Suhaila; Nik Idris, Nik Ruzni (AIP Publishing, 2016)
The impact of soy intake on breast cancer risk has been investigated extensively. However, these studies reported conflicting results. The objective of this study is to perform comprehensive review and updated meta-analysis on the association between soy intake and breast cancer risk and to identify significant factors which may contribute to the inconsistencies of results of the individual studies. Based on reviews of existing meta-analysis, we identified four main factors which contributed to the inconsistencies of results of individual studies on the association of soy intake and breast cancer risk namely; region, menopausal status of the patients, soy type and study design. Accordingly, we performed an updated meta-analysis of 57 studies grouped by the identified factors. Pooled ORs of studies carried out in Asian countries suggested that soy isoflavones consumption was inversely associated with the risk of breast cancer among both pre and postmenopausal women (OR=0.63, 95% CI: 0.54-0.74 for premenopausal women; OR=0.63, 95% CI: 0.52-0.75 for postmenopausal women). However, pooled OR of studies carried out in Western countries shows that there is no statistically significant association between soy intake and breast cancer risk (OR=0.98, 95% CI: 0.93-1.03). Our study suggests that soy food intake is associated with significantly reduced risk of breast cancer for women in Asian but not in Western countries. Further epidemiological studies need to be conducted with more comprehensive information about the dietary intake and relative exposure among the women in these two different regions.